Investigation of heavy metal concentration, origin, and relationships in Sistan region dust: A novel approach with advanced statistical analysis - Seyed Mohammad Sadeq Tabib Loghmani; Mohammad Reza Rezaei Kahkha; Ahmad Sharafti; Amin Reza Neshat (آلودگی‌های محیطی و توسعه پایدار شهری)
This study investigates the concentrations and origins of heavy metals in dust from the Sistan region in southeastern Iran. Dust samples were collected over a year from 14 stations across urban, rural, industrial, and agricultural areas. The concentrations of 14 heavy metals were determined using atomic absorption spectrometry. The results indicated that manganese had the highest average concentration (463.01 mg/kg), while molybdenum had the lowest (1.79 mg/kg). Significant seasonal variations were observed, with the highest concentrations recorded in summer. Enrichment factors (EF) for arsenic, chromium, and vanadium were calculated as 2.8, 2.3, and 2.1, respectively, signifying moderate enrichment. The pollution index (PI) also reflected moderate pollution for these elements. Principal component analysis (PCA) revealed that the first two components accounted for 94.8% of the data variability. Relationships among elements showed that nonlinear models often provided better fits, with higher R² values (e.g., 0.81 for chromium) and lower mean squared errors (MSE). Analysis of variance (ANOVA) demonstrated significant monthly variations (p<0.001) for 7 of the 14 elements. This comprehensive and innovative study enhances understanding of heavy metal contamination in the Sistan region's dust. Its findings can support the development of more effective pollution management strategies and contribute to protecting public health in the area.